2014
DOI: 10.1021/ac5004294
|View full text |Cite
|
Sign up to set email alerts
|

Wire, Mesh, and Fiber Electrodes for Paper-Based Electroanalytical Devices

Abstract: Here, we report the use of microwire and mesh working electrodes in paper analytical devices fabricated by origami paper folding (oPADs). The important new result is that Au wires and carbon fibers having diameters ranging from micrometers to tens of micrometers can be incorporated into oPADs and that their electrochemical characteristics are consistent with the results of finite element simulations. These electrodes are fully compatible with both hollow channels and paper channels filled with cellulose fibers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 53 publications
0
60
0
3
Order By: Relevance
“…42,43 Fosdick et al have reported the use of gold and carbon microwires as electrodes, and showed that they can be integrated with microfluidic paper-based analytical devices. 7 Stainless steel has been used as a material for auxiliary and quasireference electrodes in electroanalytical flow systems and other electrochemical applications. 39 Fernández-Abedul et al reported a flow system in which a hollow stainless-steel cylinder acted as both the outlet of the flow and the auxillary electrode.…”
mentioning
confidence: 99%
“…42,43 Fosdick et al have reported the use of gold and carbon microwires as electrodes, and showed that they can be integrated with microfluidic paper-based analytical devices. 7 Stainless steel has been used as a material for auxiliary and quasireference electrodes in electroanalytical flow systems and other electrochemical applications. 39 Fernández-Abedul et al reported a flow system in which a hollow stainless-steel cylinder acted as both the outlet of the flow and the auxillary electrode.…”
mentioning
confidence: 99%
“…Recently, Crooks and coworkers fabricated ePADs with cylindrical microwire electrodes [24] using a similar concept to that reported by Garcia et al for polydimethylsiloxane (PDMS) microfluidic devices [25]. Microwires have many advantageous characteristics including high conductivity, ease of modification, and availability in many different pure and alloyed compositions.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
“…They can also be cleaned and modified prior to incorporation using chemicals and solutions that cannot be used with ink, paste, or sputter-coated electrodes without contaminating or destroying the ePADs. The ePAD fabricated by Crooks et al, for example, used piranha solution (mixture of hydrogen peroxide and sulfuric acid) and subsequently modified electrodes with a self-assembled monolayer (SAM) prior to incorporation into the device [24]. Another advantage of incorporating an electrode with a micron-scale dimension is enhanced mass transport due to radial diffusion, leading to increased current density that should provide improved sensitivities and detection limits [26,27].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Para uso de eletrodos carbonáceos, além do uso de tinta condutiva, há trabalhos que fazem o uso do grafite [44,45] e da pintura direta no papel com minas de grafite [46][47][48]. Uma abordagem alternativa é o uso de fios metálicos fixados sobre a superfície do substrato de papel [49,50].…”
Section:  Análises Químicas Tradicionais De Drogas De Abusounclassified
“…No campo que concerne o desenvolvimento de sensores eletroquímicos descartáveis e portáteis, há diversas pesquisas realizadas na literatura para a fabricação de eletrodos do tipo impressos através de diferentes tecnologias, mas basicamente utilizando tintas condutivas de carbono e outros metais [125][126][127], utilizando fios metálicos [49,128], construção de dispositivos em circuitos eletrônicos [78,129], confecção a partir de CDs (CDtrodos) [130][131][132], utilização direta de grafites [45,101] ou ainda "pintando/desenhando" com grafite sobre um substrato, comumente papel [47,48], entre outras formas.…”
Section: Preâmbulounclassified